2017
DOI: 10.1097/psy.0000000000000475
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Narrative Expressive Writing on Heart Rate, Heart Rate Variability, and Blood Pressure After Marital Separation

Abstract: Objective Divorce is a common stressor that is associated with increased risk for poor long-term physical and mental health. Using an experimental design, the current study examined the impact of expressive writing (EW) on average heart rate (HR), heart rate variability (HRV), and blood pressure (BP) 7.5 months later. Methods Participants from a community sample of recently separated adults (N=109) were assigned to one of three conditions, traditional EW, narrative EW, or a control writing condition, and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The expressive writing paradigm promotes disclosure of emotional content, likely initiating a meaning making process surrounding the stressful life event (Bourassa, Allen, Mehl, & Sbarra, 2017). This emotional disclosure typically leads to psychophysiological arousal, associated with short-term distress and negative mood (McGuire, Greenberg & Gevirtz, 2005;Pennebaker, Kiecolt-Glaser, & Glaser, 1988).…”
Section: Real-time Psychophysiological and Writing Correlates Of Expressive Writingmentioning
confidence: 99%
“…The expressive writing paradigm promotes disclosure of emotional content, likely initiating a meaning making process surrounding the stressful life event (Bourassa, Allen, Mehl, & Sbarra, 2017). This emotional disclosure typically leads to psychophysiological arousal, associated with short-term distress and negative mood (McGuire, Greenberg & Gevirtz, 2005;Pennebaker, Kiecolt-Glaser, & Glaser, 1988).…”
Section: Real-time Psychophysiological and Writing Correlates Of Expressive Writingmentioning
confidence: 99%
“…Thus, the effect sizes were less than small (δ < .20) in Hypochondriasis and Depression, with a probability of being classified as a clinical case (U2) of .013 and .012 in Hypochondriasis and Depression, rates below the general population (between .05 and .07 [Somatic Symptom Disorder]; and between .013 and .10 [Illness Anxiety Disorder] in Hypochondriasis, and around .07 in non-persistent depression) (APA, 2013). Second, self-reports close to normality in Depression and Hypochondriasis are indicators of denial of symptoms as couple break-down is strongly related to negative outcomes in Depression and Hypochondriasis (Afifi et al, 2006;Amato, 2010;APA, 2013;Blanco et al, 2017;Bourassa et al, 2017;Seijo et al, 2016;Zella, 2017). Succinctly, on these two dimensions, parents in child custody litigation concealed (feigned) clinical symptomatology depressive and somatic symptoms, and anxiety owing to illness (hypochondriasis passed to be renamed in DSM-5 as Somatic Symptom Disorder and Illness Anxiety Disorder).…”
Section: Discussionmentioning
confidence: 99%
“…Both separation and divorce entail injury in the psychological adjustment of both parents and their offspring, in particular in terms of high levels of anxiety and depressive symptoms, and in the diagnosis of anxiety and depression (Afifi, Cox, & Enns, 2006;Amato, 2010;APA, 2013;Blanco, Otero, López, Torres, & Vázquez, 2017;Bourassa, Allen, Mehl, & Sbarra, 2017;Seijo, Fariña, Corras, Novo, & Arce, 2016;Zella, 2017). However, evaluations in forensic setting have found that, in general, subjects under evaluation reported normality.…”
Section: Introductionmentioning
confidence: 99%
“…Narrative writing exercises have provided help for patients with heart problems, cancer, traumatic experiences, asthma, and rheumatoid arthritis [14][15][16][17][18]. These studies reported benefits "including decreased pain, improved health status or well-being, increased vigor, better sleep quality, and decreased doctor-visit rates.…”
Section: Narrative Medicine: a Communication Therapymentioning
confidence: 99%